Synthesis of Chitosan-Coated Magnetic Microparticle Using Glutaraldehyde as Crosslinker and PEG as Spacer Arm and Its Application as Adsorbent of Peat Humic Acid - Uripto Trisno Santoso; R. Rodiansono; Ahmad Budi Junaidi; Dewi Umaningrum (Center for Journal Management and Publication, 2015)
A simple procedure for synthesis of chitosan-coated magnetic microparticle (CMMP) using glutaraldehydeas a cross-linker and polyethylene glycol (PEG) as a spacer arm has been developed. The functionalizedmicroparticle were prepared using an inexpensive, simple, rapid, one-pot process, based on the heating ofchitosan, PEG, and ferrous sulfate mixture at high pH. X-ray diffraction results indicated that the surfacemodifiedFe3O4 microparticle did not lead to phase change unlike the pure Fe3O4. Magnetic chitosanadsorbent has been evaluated for removal of peat humic acid from its aqueous solution.